Penerapan Metode Problem Solving Untuk Meningkatkan Kreativitas Dan Prestasi Belajar Statistika - Hidayati Hidayati (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2017)
The purpuse of this research is to determine the application of problem solving methods that can improve the creativity and achievvement studying statistics of science education student of FKIP UST Yogyakarta academic year. The methode of research is classroom action research consisting of four components of action that is planning, action implementation, observation and reflection. Data can be form of observation sheet, questionnaire and interview result and statistical achievement test. Quantitative data analysis technikques are calculated by descriptive statistics. The result shows 1. Student creativity increment 15.41 at cycle I and 15.71 at cycle II. Avarege percentage of pre cycle 52.90 with medium cotegory, in cycle I 68.30 with high category, and in cycle II 84.02 with high category. There was an increase in statistical achievement 25.97 in cycle I and 17.90 in cycle II. The average pre cycle score were 48.53, in cycle I 74.50 and cycle II 92.40.